DNA TEST AS AN EVIDENCE TO SUBSTITUTE FOUR WITNESSES: ANALYSIS OF ACEH QANUN NUMBER 6 OF 2014 CONCERNING JINAYAH LAW - Era Fadli; Mursyid Djawas; Syarifah Rahmatillah (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2018)
Ulema agrees on two pieces of adultery evidence, namely confession and four witnesses. Today, DNA test evidence is also considered to be accurate in determining someone committing adultery. Aceh Qanun Number 6 of the Year 2014 concerning Law of Jinayat (criminal law) has included DNA test as evidence to replace the four witnesses. This research was conducted using a literature study approach with the juridical-analysis method. The results confirmed that Acehnese People want clear and constitutional rules regarding law enforcement, following up the privileges granted by the central government in establishing sharia law. The DNA test results can be used as evidence to replace four witnesses. Based on sharia law, the adultery can be proved by two alternative pieces of evidence, iqrār (admission/confession) and shahadah (testimony of witnesses). However, DNA test is not mentioned clearly in the Qur’an, hadith or the opinions of scholars. In sharia law, a DNA test can be included as the type of supporting and additional evidence like pregnancy and childbirth beyond the minimum pregnancy limit. The supporting and additional evidence, such as the DNA result cannot replace the four witnesses. Abstrak: Terdapat dua alat bukti zina yang telah disepakati oleh ulama, yaitu pengakuan dan empat orang saksi. Dewasa ini, terdapat alat bukti lain yang dipandang akurat menetapkan seseorang berbuat zina, yaitu bukti test DNA. Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat telah memasukkan test DNA sebagai alat bukti pengganti empat orang saksi. Penelitian ini dilakukan dengan pendekatan studi pustaka dengan metode analisis-yuridis. Hasil penelitian ini menegaskan bahwa masyarakat Aceh menginginkan adanya aturan yang jelas dan konstitusional tentang penegakan hukum, sebagai tindak lanjut dari keistimewaan yang diberikan oleh pemerintah pusat dalam menegakkan syari’at Islam. Hasil test DNA tersebut bisa menjadi alat bukti untuk menggantikan empat orang saksi. Menurut Hukum Islam pembuktian zina dapat dilakukan dengan dua alat bukti yaitu iqrār dan syahadah. Kedua alat bukti ini bersifat alternatif. Sementara test DNA tidak disebutkan secara pasti dalam Alquran dan hadis serta pendapat ulama. Test DNA dalam hukum Islam bisa masuk dalam jenis alat bukti pendukung dan tambahan seperti halnya kehamilan dan kelahiran anak di luar batas minimal kehamilan. Alat bukti pendukung dan tambahan seperti hasil test DNA tidak bisa menggantikan empat orang saksi. Kata Kunci: Tes DNA, Alat Bukti Pengganti, Empat Orang Saksi, Qanun Jinayah